A literature review about Argentinian educational management in times of change - Vicente, María Eugenia (2016)
The aim of this article is to collect appropriate information on the characteristics of educational anagement in times of reforms or changes in its institutional structures. This review adopts a descriptive qualitative methodology and applies documentary analysis as a technique to identify, describe and represent the content of the documents in a way other than the originals’, in order to enable its diffusion and use for other research studies and documents on educational management. The findings are intended to participate in a discussion about the set of routines, habits and institutional practices that form educational management in times of reform.